Caffeic acid phenethyl ester modulates Helicobacter pylori-induced nuclear factor-kappa B and activator protein-1 expression in gastric epithelial cells - KELLEHER, DERMOT P; SABRA, KAMAL; WINDLE, HENRY (Nature, 2005)
Caffeic acid phenethyl ester (CAPE), an active component of propolis from honeybee hives (honeybee resin), has anti-inflammatory, anti-carcinogenic and anti-bacterial properties. This study was designed to investigate the anti-inflammatory effects of CAPE on Helicobacter pylori-induced NF-kappaB and AP-1 in the gastric epithelial cell line AGS. Electrophoretic mobility shift assay was used to measure NF-kappaB- and AP-1-DNA binding activity. Western blotting was used to detect IkappaB-alpha and COX-2 expression in AGS cells cocultured with H. pylori. The antiproliferative effect of CAPE was measured by MTT assay. Our results showed that caffeic phenethyl ester inhibits H. pylori-induced NF-kappaB and AP-1 DNA-binding activity in a dose (0.1-25 microg ml(-1) approximately 0.35-88 microM) and time- (15-240 min) dependent manner in AGS cells. Maximum inhibition by CAPE was observed at concentrations of 25 microg ml(-1) ( approximately 88 microM) CAPE prevented H. pylori- and cytokine-induced degradation of IkappaB-alpha protein. Pretreatment of AGS cells with CAPE also blocked cytokine- and mitogen-induced NF-kappaB and AP-1 expression. Furthermore, CAPE suppressed H. pylori-induced cell proliferation and production of the cytokines TNF-alpha and IL-8. In addition, CAPE blocked H. pylori-induced COX-2 expression. The inhibition of such transcription by CAPE could result in suppression of many genes during H. pylori-induced inflammation, and also provide new insights into the anti-cancer and anti-inflammatory properties of CAPE.
PUBLISHED
Keywords: Clinical Medicine